Cover Image. (24th February 2020) - Brinchmann, B.; Widding‐Havneraas, T.; Modini, M.; Rinaldi, M.; Moe, C. F.; McDaid, D.; Park, A‐L.; Killackey, E.; Harvey, S. B.; Mykletun, A.
Abstract : The cover image is based on the Meta Analysis A meta‐regression of the impact of policy on the efficacy of Individual Placement and Support by Beate Brinchmann, Miles Rinaldi, DAVID MCDAID et al., https://doi.org/10.1111/acps.13129 .